Value of T2 Mapping MRI for Prostate Cancer Detection and Classification. Issue 2 (17th January 2022) - Klingebiel, Maximilian; Schimmöller, Lars; Weiland, Elisabeth; Franiel, Tobias; Jannusch, Kai; Kirchner, Julian; Hilbert, Tom; Strecker, Ralph; Arsov, Christian; Wittsack, Hans‐Jörg; Albers, Peter; Antoch, Gerald; et al.
Abstract : Background: Currently, multi‐parametric prostate MRI (mpMRI) consists of a qualitative T2, diffusion weighted, and dynamic contrast enhanced imaging. Quantification of T2 imaging might further standardize PCa detection and support artificial intelligence solutions. Purpose: To evaluate the value of T2 mapping to detect prostate cancer (PCa) and to differentiate PCa aggressiveness. Study Type: Retrospective single center cohort study. Population: Forty‐four consecutive patients (mean age 67 years; median PSA 7.9 ng/mL) with mpMRI and verified PCa by subsequent targeted plus systematic MR/ultrasound (US)‐fusion biopsy from February 2019 to December 2019. Field Strength/Sequence: Standardized mpMRI at 3 T with an additionally acquired T2 mapping sequence. Assessment: Primary endpoint was the analysis of quantitative T2 values and contrast differences/ratios (CD/CR) between PCa and benign tissue. Secondary objectives were the correlation between T2 values, ISUP grade, apparent diffusion coefficient (ADC) value, and PI‐RADS, and the evaluation of thresholds for differentiating PCa and clinically significant PCa (csPCa). Statistical Tests: Mann–Whitney test, Spearman's rank ( r s ) correlation, receiver operating curves, Youden's index (J), and AUC were performed. Statistical significance was defined as P < 0.05. Results: Median quantitative T2 values were significantly lower for PCa in PZ (85 msec) and PCa in TZ (75 msec) compared to benign PZ (141 msec) or TZ (97 msec) ( P < 0.001). CD/CR between PCa and benign PZ (51.2/1.77), respectively TZ (19.8/1.29), differed significantly ( P < 0.001). The best T2 ‐mapping threshold for PCa/csPCa detection was for TZ 81/86 msec (J = 0.929/1.0), and for PZ 110 msec (J = 0.834/0.905). Quantitative T2 values of PCa did not correlate significantly with the ISUP grade ( r s = 0.186; P = 0.226), ADC value ( r s = 0.138; P = 0.372), or PI‐RADS ( r s = 0.132; P = 0.392). Data Conclusion: Quantitative T2 values could differentiate PCa in TZ and PZ and might support standardization of mpMRI of the prostate. Different thresholds seem to apply for PZ and TZ lesions. However, in the present study quantitative T2 values were not able to indicate PCa aggressiveness. Level of Evidence: 2 Technical Efficacy: Stage 2